Density Resilient-Modulus Correlation in Stone Mastic Asphalt Mixture Using Automated Roller Compactor - Soleimani Zadeh, Ehsan (2009)
Resilient or stiffness modulus (MR) is the key property that has been utilized to characterize asphalt mixture and other structural properties for flexible pavement design. MR is generally obtained by testing laboratory compacted samples which are compacted to a density similar to that achieved in the field under traffic. However, resilient modulus test has been considered as a complex, timeconsuming, and expensive experiment. In addition, the poor simulation of field compaction by the present compaction methods may results in less accurate and unrealistic data for pavement design, especially in SMA mixtures. Hence, the main objective of this study was to develop correlation between density and resilient modulus properties of Stone Mastic Asphalt (SMA) slabs compacted using a newly developed roller compactor named Turamesin. Turamesin, which has proven to be capable of simulating field compaction conditions in the laboratory, is also able to produce laboratory samples with desired density and uniformly distributed properties. To come up with research objectives, total numbers of five slabs with different targeted level of air voids were prepared and core specimens were subjected to different tests of bulk density, air voids, resilient modulus (at 25°C and 40°C), Marshall stability, and flow. Statistical methods including regression analysis were then conducted and from the results, it was found that the stiffness properties of Turamesin compacted SMA slabs are directly affected by physical and volumetric properties of mixtures in terms of density and air voids. To correlate density with MR at 25°C and 40°C, two different equations were developed. These findings then were employed to establish guideline on density-resilient modulus which is included with two main and two imaginary line, making possible to determine MR of the mixture at any temperature of 25°C, 30°C, 35°C, and 40°C without need to conduct a complex, time-consuming, and expensive resilient modulus test.